Japan-Uzbekistan Diplomatic Relations History - Zuhayriddin Tuychiyevich , Bozorov (Universitas Muhammadiyah Sidoarjo, 2019)
Over the years of independence, the Republic of Uzbekistan has established diplomatic relations with developed countries of the world and has taken a step towards mutually beneficial cooperation. In this article, Uzbekistan cooperates with Japan in political, socio-economic, cultural and humanitarian spheres